PERANAN EKSTRAKURIKULER ANGKLUNG DALAM MEMUPUK SEMANGAT KEBANGSAAN DI SMP PASUNDAN 1 BANDUNG - Najmi Putri Arifin, Alya; Sapriya; Bestari, Prayoga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of the angklung extracurricular activity as a medium for strengthening nationalism character based on the third principle of Pancasila at SMP Pasundan 1 Bandung. This research employed a descriptive method with a qualitative approach. The research subjects consisted of the extracurricular supervisor, teachers, and students who actively participated in the angklung extracurricular activity. Data collection was carried out using a descriptive method with a qualitative approach through observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the angklung extracurricular activity plays an important role in instilling national values ​​among students, including introducing national culture, fostering pride in national identity, developing the values ​​of togetherness and unity in accordance with the third principle of Pancasila, and increasing awareness of cultural preservation. Although there are several obstacles, such as limited practice time and the influence of popular culture, this activity continues to make a significant contribution to the development of students' nationalism character. Therefore, the angklung extracurricular activity functions not only as an artistic activity but also as an effective medium of character education in fostering the spirit of nationalism among the younger generation.